Global raw materials issues and their impact on polish economy - Katarzyna Idzkowska (Institute of Economic Research (IER), 2015)
This research concentrate on an irregular distribution of energy resources in the world and also on the problem of scarcity of non-renewable raw materials, such as petroleum, natural gas, charcoal. The main purpose of the article is to describe a topical fossil fuels market's situation and to present prognosis about the future of natural resources' extraction. The consequences of limited energy resources using in Poland is also an important issue. The author carried out an analysis of a secondary data that is published in annual British Petroleum reports: 'Energy Outlook 2035: February 2015' and 'BP Statistical Review of World Energy', that are about energy production, consumption and trade. Along with the limited resources increase, the price increase as well. By the end of 2013 year, a petroleum's barely cost 110 USD, whereas 10 years ago the cost was 30 USD. Even though the recent world's energy demand has decreased, within next 50-60 years petroleum and gas loads may exhaust, being an effect of an intensive extraction. A difficult situation on an fossil fuels market also has its effects on polish economy. Due to a high dependency on an abroad load supply (especially of natural gas - 70% and oil - 99%) and a constantly growth of the prices, energy safety in Poland is seriously endangered.
Keywords: L71; O13; Q32; 330; fossil resources; non-renewable raw materials; resource scarcity